Peran Media dalam Menyebar Luaskan Dakwah di Platform Media Sosial - Efendi, Erwan; Sahtriani, Mely; Noprialdi, Rama (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
In the modern era, communication media is very important for spreading religious messages because they can be received simultaneously on social media such as YouTube, Instagram, TikTok, and so on, and it becomes easier for preachers to convey religious messages more effectively. The aim of this research is to find out the role of the media in spreading da'wah on social media with the Instagram and Youtube accounts @buyayahya. This research was conducted using a descriptive and qualitative approach. Data is collected through observation and documentation. Then, the data is evaluated through reduction, presentation and drawing conclusions. This study shows that Buya Yahya's Instagram and Youtube accounts use social media as a tool for da'wah. Buya Yahya always includes a da'wah message in every upload, both in the form of photos and videos edited in an attractive way, using all Instagram features to attract new followers and users